Geometric Influence of Local Road on Safety: A Bibliometric Literatur Review - Dejan Fauzan Azhary; Rio Satrio; Anisa Awaliyah; Abdul Kholiq; Muhammad isradi (LEADER: Civil Engineering and Architecture Journal, 2025)
Road geometry plays a pivotal role in shaping traffic safety outcomes, especially in developing regions experiencing rapid motorization. This study employs a bibliometric analysis to explore the trends, key themes, and research developments surrounding the influence of geometric road design on local road safety. Drawing data from the Scopus and Google Scholar databases via the Publish or Perish tool, the analysis is visualized using VOSviewer software to map keyword networks, author collaborations, and institutional linkages. The results reveal five dominant research clusters, ranging from road safety and driver behavior to technological approaches in traffic analysis. The overlay and density visualizations illustrate the evolution and concentration of thematic interests, with increasing attention given to geometric variables like curvature, alignment, and lane width in recent years. This research highlights significant gaps in contextual studies, especially in middle-income regions such as Indonesia, providing a foundation for future applied investigations in road safety engineering.